HDQ-FD integrated methodology for nonlinear static and dynamic response of doubly curved shallow shells - Civalek, Ömer; Ülker, Mehmet (Techno-Press, 2005)
The non-linear static and dynamic response of doubly curved thin isotropic shells has been studied for the step and sinusoidal loadings. Dynamic analogues Von Karman-Donnel type shell equations are used. Clamped immovable and simply supported immovable boundary conditions are considered. The governing nonlinear partial differential equations of the shell are discretized in space and time domains using the harmonic differential quadrature (HDQ) and finite differences (FD) methods, respectively. The accuracy of the proposed HDQ-FD coupled methodology is demonstrated by the numerical examples. Numerical examples demonstrate the satisfactory accuracy, efficiency and versatility of the presented approach.
Keywords: Coupled methodology; Doubly curved shells; Harmonic differential quadrature; Non-linear dynamic analysis